Aqueous amine solution characterization for post-combustion CO2 capture process. (1st January 2017) - El Hadri, Nabil; Quang, Dang Viet; Goetheer, Earl L.V.; Abu Zahra, Mohammad R.M.
Highlights: The CO2 solubility of 30 aqueous amine solutions was measured at 30 wt% and 313.15 K. The CO2 loading of HMD is the highest, and that of TEA is the lowest. 2DMAE, 3DMA1P, 1DMA2P, MDEA, TMPAD and 2EAE have a low heat of absorption with CO2 . 2EAE can be used as an alternative to MEA in the CO2 capture process. Abstract: This article presents a thermodynamic and kinetic characterization of CO2 absorption by 30 aqueous amine solutions. A solvent screening setup (S.S.S.) was used to find the CO2 loading ( α ) for 30 different aqueous amine solutions (30 wt%) at a pressure of 1 bar with feed gas containing 15 vol% CO2 and 85 vol% N2 at 313.15 K to provide reliable absorber parameters. The structures of various amines (linear, non-linear, polyamines, sterically hindered, etc.) were tested and the S.S.S. results showed that hexamethylenediamine (HMD) has higher CO2 loading at 1.35 moles of CO2 /mole of amine, and triethanolamine (TEA) has the lowest at 0.39 mole of CO2 /mole of amine. The heat of absorption indicates that MDEA has the lowest and HMD has the highest at −52.51 kJ/mole of CO2 and −98.39 kJ/mole of CO2, respectively. The combined data for the CO2 loading and the absorption heat generated 6 amines that have good properties for the post-combustion CO2 capture process in comparison with that of MEA. These amines are made up of one secondary amine (2-ethylaminoethanol, 2EAE) and 5 tertiary amines (N-methyldiethanolamine, MDEA, 1-dimethylamino-2-propanol, 1DMA2P, 2-dimethylaminoethanol, 2DMAE, 3-dimethylamino-1-propanol, 3DMA1P and N, N, N′, N′-tetramethyl-1, 3-propanediamine, TMPDA). In comparison with the amine reference MEA (Δ H  = −85.13 kJ/mole of CO2 and α  = 0.58 mole CO2 /mole of amine), the 6 amines have heats of absorption that are between −68.95 kJ/mole of CO2 and −52.51 kJ/mole of CO2, and their CO2 loading is between 0.52 and 1.16 mole of CO2 /mole amine. The third important parameter, namely the reaction kinetics between aqueous amine solutions and CO2, was studied by using stopped-flow equipment to measure the pseudo-first order reaction ( k 0, s −1 ) at different amine concentrations. A determination of the second order rate constants ( k 2, m 3  mole −1  s −1 ) at 298.15, 303.15, 308.15 and 313.15 K was performed by using the proposed reaction mechanisms. The base catalysis mechanism was used to correlate the experimental data of the tertiary amines and the zwitterion mechanism was used to correlate the experimental data of the primary/secondary amines. The kinetics results show that 2EAE, a secondary amine, was very high in comparison with MDEA, 1DMA2P, 2DMAE, 3DMA1P and TMPDA, all of which are tertiary amines that are very close to MEA, which is the reference case. This result shows that 2EAE is a good candidate for CO2 capture as an alternative to MEA because it has good CO2 absorption, a low heat of absorption and high kinetic reaction with CO2 . Moreover, the outcomes for the thermodynamic and kinetic properties indicate that the following 5 amine blends have emerged from this study: 2EAE/MDEA, 2EAE/1DMA2P, 2EAE/2DMAE, 2EAE/3DMA1P and 2EAE/TMPDA.